2020
DOI: 10.1128/aem.02730-19
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotics Inhibit Proteolysis by Gut Bacteria in a Host Diet-Dependent Manner: a Three-Stage Continuous In Vitro Gut Model Experiment

Abstract: Dietary protein residue can result in microbial generation of various toxic metabolites in the gut, such as ammonia. A prebiotic is “a substrate that is selectively utilised by host microorganisms conferring a health benefit” (G. R. Gibson, R. Hutkins, M. E. Sanders, S. L. Prescott, et al., Nat Rev Gastroenterol Hepatol 14:491–502, 2017, https://doi.org/10.1038/nrgastro.2017.75). Prebiotics are carbohydrates that may have the potential to reverse the harmful effects of gut bacterial protein fermentation. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 47 publications
3
29
0
Order By: Relevance
“…It served as a vehicle control in this study, but also mimicked a gut environment that was devoid of carbohydrate, but rich in proteins. The increase in C. perfringens, along with smaller increases in other Firmicutes families and Bacteroides spp., supports a metabolomic profile rich in propionate, butyrate, and branched-chain fatty acids such as isobutyrate and isovalerate, characteristic of the degradation of glycoproteins or proteins that reach the distal gut [26,80]. The ingredients were able to suppress C. perfringens [81], a potential pathogen, and this may be attributed to the increase in other beneficial bacteria.…”
Section: Discussionmentioning
confidence: 67%
“…It served as a vehicle control in this study, but also mimicked a gut environment that was devoid of carbohydrate, but rich in proteins. The increase in C. perfringens, along with smaller increases in other Firmicutes families and Bacteroides spp., supports a metabolomic profile rich in propionate, butyrate, and branched-chain fatty acids such as isobutyrate and isovalerate, characteristic of the degradation of glycoproteins or proteins that reach the distal gut [26,80]. The ingredients were able to suppress C. perfringens [81], a potential pathogen, and this may be attributed to the increase in other beneficial bacteria.…”
Section: Discussionmentioning
confidence: 67%
“…Fecal donations were obtained from three healthy donors, two females and one male aged between 30 and 45 y [12,[21][22][23]. Donors did not undergo antibiotic treatment for at least 3 months prior to stool collection, did not intentionally consume pre-or probiotic supplements before the experiment, and had no history of bowel disorders.…”
Section: Fecal Donorsmentioning
confidence: 99%
“…The action of a prebiotic on the colon microbiota is a complex phenomenon, and for its comprehension, a complex experimental model capable of considering many different parameters of the ecology of colon microbiota is necessary. In particular, the study of certain bacterial taxa and that of healthy compounds derived from fiber degradation, namely short-chain fatty acids (SCFAs) [9] or medium-chain fatty acids (MCFAs) [10], or harmful ones derived from proteolytic fermentation, namely Indole, skatole [11], and branched-chain fatty acids (BCFAs) [12] may represent a robust strategy. The presence of these compounds derived from fiber degradation by colon microbiota should tell if the fiber evaluated fosters those beneficial bacterial groups involved in fiber fermentation rather than those involved in harmful proteolytic fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research demonstrated that prebiotic supplementation with inulin was associated with increased relative abundance of bifidobacteria and decreased levels of proteolytic metabolic products including ammonia and branched chain fatty acids in human fecal samples [121]. Consumption of fermented foods may also contribute to a protective metabolic environment due to their probiotic contents, notably Lactobacillus casei CRL431 [122][123][124][125].…”
Section: Diet Prebiotics and Probiotics In Relationship To Breast Cmentioning
confidence: 99%